2009
DOI: 10.1002/anie.200901279
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic and Surface‐Electrocatalytic Water Oxidation by Redox Mediator–Catalyst Assemblies

Abstract: We recently described single-site catalysts for water oxidation that operate by a well-defined mechanism involving stepwise three-electron oxidation to high-oxidation-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
2
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(110 citation statements)
references
References 10 publications
3
102
2
3
Order By: Relevance
“…Measurement of oxygen produced has not yet been reported for the TiO 2 -bound molecular assembly, but catalytic current was seen for the [Ru(Mebim 2 py)(4,4’-(CH 2 PO(OH 2 ) 2 ) 2 (bpy))(OH 2 )] 2+ catalyst without the chromophore on a nano ITO surface [183]. …”
Section: Catalysis For Light-driven Water Oxidationmentioning
confidence: 99%
“…Measurement of oxygen produced has not yet been reported for the TiO 2 -bound molecular assembly, but catalytic current was seen for the [Ru(Mebim 2 py)(4,4’-(CH 2 PO(OH 2 ) 2 ) 2 (bpy))(OH 2 )] 2+ catalyst without the chromophore on a nano ITO surface [183]. …”
Section: Catalysis For Light-driven Water Oxidationmentioning
confidence: 99%
“…For example,M eyer and co-workersl ater demonstrated the electrocatalytic water oxidation of an adsorbed m-oxo-bridgedr uthenium complex, [49] as well as single-site ruthenium complexes using phosphonates as the anchoring groups ( Figure 6). [58][59][60][61] Although the turnover at smalloverpotential is not satisfactory, the authors demonstrated the importance of using ar edox mediator, [58,60] PCET, [58] and as ingle ET activation of multiple ETs/watero xidation. [49] Further details on the photoelectro-chemicalo xidation of water on the surfaces of metal oxide electrode materials are discussed in alater section.…”
Section: Electrocatalytic Water Oxidationmentioning
confidence: 99%
“…The example shown is also impressive as a catalyst both in terms of rate and stability with no sign of deterioration after 28 000 turnovers. An electrochemical study of the surface-bound catalyst reveals a mechanism analogous to the single-site mechanism in Scheme 6 with the surface RuIII/II couple appearing at 1.33 V in 0.1 M HNO 3 [63].…”
Section: Chromophore Catalyst Assemblies On Oxide Surfacesmentioning
confidence: 93%